99.5k views
0 votes
Evaluate 3^2 + (7 − 2) ⋅ 4 − 6 over 3

User HyperioN
by
4.6k points

2 Answers

3 votes

Answer:

7.7

Explanation:

we basically follow the BEDMAS rule

1st we workout the bracket (7-2)=5

2nd the exponent 3^2=9

3rd the multiplication (7-2) . 4 = 5 . 4 = 20

4th addition 9+20=29

5th step is subtraction 29-6=23

the final step is dividing 23 by 3, which will become 7.7

User Xingou
by
4.9k points
5 votes

Answer: 27

Explanation:

Use PEMDAS

3² + (7 - 2) · 4 - 6/3

Parenthesis: ↓

3² + 5 · 4 - 6/3

Exponents: ↓

9 + 5 · 4 - 6/3

Multiplication & Division: ↓ ↓

9 + 20 - 2

Addition & Subtraction: ↓ ↓

29 - 2 = 27

User Aytek
by
5.5k points